IMPLEMENTATION OF THE ELABORATION LIKELIHOOD MODEL (ELM) IN THE POLITICAL COMMUNICATION STRATEGY OF THE JAYA-WIBAWA PAIR ON INSTAGRAM IN THE 2024 DENPASAR REGIONAL ELECTION - Bayu Nata Negara; Pratiwi, Nuning Indah; Joniarta, I Wayan; Latupeirissa, Jonathan Jacob Paul (Fakultas Ushuluddin Adab dan Dakwah Insitut Agama Islam Negeri Kerinci, 2025)
This study examines the political communication strategies of the Jaya-Wibawa couple to form their leadership image through the @jayawibawadenpasar Instagram account in the 2024 Denpasar Regional Elections, based on the Elaboration Likelihood Model (ELM) framework. The methodology used is qualitative descriptive, which is carried out by observing the content and responses from the comment column, completing digital documentation, literature studies, and conducting in-depth interviews with members of the Jaya-Wibawa couple's campaign team. The findings of this study indicate that this couple's communication approach is built on two main categories, namely incidental content and persuasive content, which complement each other to achieve engagement and appeal to young voters. The application of ELM theory can be seen in the merger of two persuasion paths. The central path emerges through data-driven content, explanations of programs, and policy arguments that encourage high elaboration, which is demonstrated by the audience's critical comments on the effectiveness of the program and the sustainability of public policy. Meanwhile, peripheral pathways are more visible through aesthetic visual elements, music, symbols of unity, and emotional touches that create a positive impression without deep analysis. The merger of these two channels of persuasion has succeeded in increasing the electability of candidate pairs. This study confirms that Instagram plays the role of an interactive and live-action political communication platform, which is able to strengthen the legitimacy of candidates and encourage the participation of young voters through a lightweight, visual, and accessible campaign approach.